Statistical methods for the detection and analysis of radioactive sources - Klumpp, John, author; Brandl, Alexander, advisor; Johnson, Thomas, committee member; Steinhauser, Georg, committee member; LaRue, Susan, committee member; Givens, Geof, committee member (Colorado State University. Libraries, 2014)
We consider four topics from areas of radioactive statistical analysis in the present study: Bayesian methods for the analysis of count rate data, analysis of energy data, a model for non-constant background count rate distributions, and a zero-inflated model of the sample count rate. The study begins with a review of Bayesian statistics and techniques for analyzing count rate data. Next, we consider a novel system for incorporating energy information into count rate measurements which searches for elevated count rates in multiple energy regions simultaneously. The system analyzes time-interval data in real time to sequentially update a probability distribution for the sample count rate. We then consider a "moving target" model of background radiation in which the instantaneous background count rate is a function of time, rather than being fixed. Unlike the sequential update system, this model assumes a large body of pre-existing data which can be analyzed retrospectively. Finally, we propose a novel Bayesian technique which allows for simultaneous source detection and count rate analysis. This technique is fully compatible with, but independent of, the sequential update system and moving target model.